The Impact of Customer Satisfaction with EWOM and Brand Equity on E-Commerce Purchase Intention in Indonesia Moderated by Culture - Angga Febrian; Muhtad Fadly (Bina Nusantara University, 2021)
The digital era, which increasingly becomes massive in people’s lives, impacts the traditional sales methods.E-commerce companies compete in winning the competition to create superior customer value. An effective andefficient marketing strategy is needed that can influence customer purchase intention. The research focused onthe effect of customer satisfaction, which created eWOM and increased brand equity on purchase intention byadding culture (collectivist culture) as the moderator variables. The research applied a quantitative approach. Thedata were obtained from 280 respondents selected by non-probability sampling. Respondents were customerswho had already bought products through e-commerce in Indonesia. The questionnaire instrument was adoptedbased on theories from the previous researchers. The data used the Likert scale and were analyzed using theSmartPLS 3.0. The results state a significant relationship between the independent and dependent variables. Allindependent variables have a significant influence on the dependent variable. However, culture as the moderatorvariable cannot get significant results in the relationship between all the variables. It gets irrelevant results. Hence,the results show that the moderator variable is more appropriate as the independent variable. It can directlyaffect purchase intention. The research contributes to testing culture as the moderator variable that makes theindependent variables generalize the findings.